Young porphyries, old zircons: new constraints on the timing of deformation and gold mineralisation in the Eastern Goldfields from SHRIMP U-Pb zircon dating at the Kanowna Belle Gold Mine, Western Australia - Ross, A.; Barley, M.; Brown, S.; McNaughton, Neal; Ridley, J.; Fletcher, Ian (Elsevier Science BV, 2004)
The Kanowna Belle Gold Mine is a Late Archaean orogenic lode-gold deposit hosted by felsic volcaniclastic and intrusive rocks (porphyries) of the Kalgoorlie Terrane, Western Australia. Rare gold occurs in fragments of veins and alteration that form clasts within the Black Flag Group volcaniclastic rocks at the Kanowna Belle mine, indicating that epithermal gold mineralisation accompanied Black Flag Group volcanism. The SHRIMP U-Pb zircon age of the volcaniclastic unit is 2668 9 Ma, and xenocrystic zircons with ~2.68, 2.70 and 2.71 Ga age groupings are common. The Black Flag Group rocks are faulted by a D1 thrust, and ~2670 Mais thus an older limit for regional D1 deformation. Although SHRIMP U-Pb zircon ages of felsic porphyries commonly give the best constraints on the timing of deformation and structurally controlled gold mineralisation, the data are complex and dates from single samples can be ambiguous. Four Porphyry samples from the Kanowna Belle Gold Mine were analysed. Back scattered electron and cathodoluminescence imaging show that most magmatic zircon in the porphyries is either high-U and metamict, or restricted to rims on older xenocrysts that are too narrow to be dated by SHRIMP. Some porphyries appear to have been saturated with zircon at source and contain only xenocrystic zircons.Zircons that are interpreted to be magmatic in a sample of the mineralised Kanowna Belle Porphyry gives a mean age of 26556 Ma. The Kanowna Belle Porphyry is cross cut by regional D2 fabrics and ~2655 Ma is thus the maximum age for regional D2 deformation. This is a maximum age for epigeneticlode-gold mineralisation. The age of resetting of high-U zircon grains (2.63 Ga) and the age of ore-related Pb-Pb galenas (2.63 Ga) serves as an approximate date for lode-gold mineralisation. If the complex zircon history of the felsic porphyries at Kanowna Belle is typical of this suite throughout the Eastern Goldfields Province, it is clear that existing single zircon dates from this Province require reevaluation, backed up by careful backscattered and cathodoluminescence imaging and textural studies.